Revision of the genus Suljuktocossus Becker-Migdisova, 1949 (Hemiptera, Palaeontinidae), with description of a new species from Daohugou, Inner Mongolia, China - Wang, Ying; Ren, Dong (Zootaxa, 2007)
In this paper a complete specimen of fossil Palaeontinidae, Suljuktocossus yinae sp. nov. from Daohugou (Jiulongshan Formation) in Inner Mongolia, China is described. This new species is established based on both complete forewings and hindwings. According to this specimen, the diagnosis of the genus Suljuktocossus is revised. Moreover, based on the distribution of the genus Suljuktocossus, we consider the age of the Daohugou biota as Middle Jurassic